Expression of vascular endothelial growth factor in human oral squamous cell carcinoma: its association with tumour progression and p53 gene status. Issue 10 (October 1998) - Maeda, T; Matsumura, S; Hiranuma, H; Jikko, A; Furukawa, S; Ishida, T; Fuchihata, H
Abstract : AIMS: To correlate vascular endothelial growth factor (VEGF) expression in oral squamous cell carcinoma with the clinicopathological characteristics and prognosis; and to assess whether p53 gene status is associated with VEGF expression in human cancers. METHODS: Tumour specimens from 45 patients with oral squamous cell carcinomas were examined. Expression of VEGF was determined using an immunohistochemical method, and a tumour was considered positive when more than 5% of the neoplastic cells showed VEGF immunoreactivity. The p53 gene status was screened using a polymerase chain reaction–single strand conformation polymorphism analysis. RESULTS: VEGF positive staining was detected in 19 (42.2%) of the 45 cases. VEGF immunoreactivity did not correlate with the histological degree of tumour differentiation, clinical stages, or lymph node metastasis. The patients with VEGF positive tumours had a significantly worse prognosis than those with VEGF negative tumours. The five year overall survival rate of the VEGF negative patients was 76.5%, as compared with 48.8% for the VEGF positive patients. No significant association between VEGF expression and the p53 gene status of the tumours was found. CONCLUSIONS: VEGF is a good prognostic indicator of the survival of patients with oral squamous cell carcinoma. The p53 gene status does not seem to be associated with VEGF expression in these cancers.